Sensitivities of Four New Commercial Hepatitis B Virus Surface Antigen (HBsAg) Assays in Detection of HBsAg Mutant Forms - Ly, Thoai Duong (American Society for Microbiology, 2006)
Mutations in hepatitis B virus surface antigen (HBsAg) involving amino acid substitution within the immunodominant “a” determinant may affect the performance of commercial HBsAg assays. The performances of four HBsAg assays that recently received Conformité Européene marking, Advia Centaur HBsAg (Bayer), Monolisa HBsAg Ultra (Bio-Rad), Liaison HBsAg (Dia Sorin), and Vidas HBsAg Ultra (bioMérieux), were compared with that of the routinely used HBsAg assay AxSYM HBsAg V2 (Abbott). Assays were evaluated for (i) analytical sensitivity performance with a national reference HBsAg panel (including 10 samples with calibrated HBsAg concentrations from 0.04 to 2.24 ng/ml) and (ii) the detection of HBsAg mutants by studying a panel of 35 HBsAg mutants (23 collected from patients and 12 recombinant mutants). The limits of detection of these assays were <0.15 ng/ml (from 0.089 to 0.121 ng/ml). The sensitivity performances for mutant virus detection varied, ranging from 37.1% to 91.4%. The lack of detection of these mutants by commercial assays was probably due to the epitope recognition of the anti-HBs assay reagents in the capture phase and in the conjugates. The prevalence and clinical impact of HBsAg mutants are under investigation. However, the manufacturers must be vigilant in the design of the assays in order to reduce the risk of missing a broad range of described S gene mutants.